Microbial Secondary Metabolites and Biotechnology - Fouillaud, Mireille; Dufossé, Laurent (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Many research teams are working to demonstrate that microorganisms can be our daily partners, due to the great diversity of biochemical transformations and molecules they are able to produce. This Special Issue highlights several facets of the production of microbial metabolites of interest. From the discovery of new strains or new bioactive molecules issued from novel environments, to the increase in their synthesis by traditional or innovative methods, different levels of biotechnological processes are addressed. Combining the new dimensions of "Omics" sciences, such as genomics, transcriptomics or metabolomics, microbial biotechnologies are opening up incredible opportunities for discovering and improving microorganisms and their production.